Pengaruh Struktur Modal, Kebijakan Dividen, dan Keputusan Investasi Terhadap Nilai Perusahaan (Studi Pada Perusahaan Sektor Industri Dasar dan Kimia Tahun 2016-2019) - Bunga Yusparipurna; Almira Devita Putri; Defia Riski Anggarini (JAAF (Journal of Applied Accounting and Finance), 2022)
This study aims to explain the effect of the variables of Capital Structure, Dividend Policy and Investment Decisions on Firm Value (a study on companies in the basic and chemical industry sectors 2016-2019). This type of research is a quantitative approach. The population of this study is the basic and chemical industrial sector companies listed on the Indonesia Stock Exchange as many as 78 companies, the determination of the sampling using purposive sampling technique through certain criteria in order to obtain a sample of 16 companies with a total of 4 years of observation. The analytical method used is the panel data regression analysis method using the Eviews 9.0 tool. The results of this study indicate that capital structure, dividend policy and investment decisions simultaneously affect firm value. While partially shows that the capital structure variable proxied by the Debt to Equity Ratio (DER) has no effect on firm value, dividend policy is proxied by the Dividend Payout Ratio (DPR) does not affect the firm value proxied by Price to Book Value. (PBV), and investment decisions proxied by Price Earning Ratio (PER) have a positive and significant effect on firm value proxied by Price to Book Value (PBV).